A Guide to a Mixed-Methods Approach to Healthcare Research - Kritika Rana; Ritesh Chimoriya (Encyclopedia, 2025)
A mixed-methods approach combines qualitative and quantitative research methodologies to provide a comprehensive understanding of complex social phenomena in healthcare. This approach leverages the strengths of both methodologies to address research questions that cannot be fully answered by a single method. While quantitative data offer measurable patterns and generalizability, qualitative research provides critical insights into the human experiences, cultural contexts, and systemic factors that underlie these patterns, and such elements are often missed by purely statistical analyses. Notably, qualitative components can uncover why interventions succeed or fail in real-world settings, adding explanatory power to quantitative results. By integrating numerical data analysis with in-depth contextual insights, mixed-methods research enables researchers to explore, explain, and generalize findings in healthcare settings more holistically than either method could achieve alone.